Progress in recent sustainable materials for greenhouse gas (NOx and SOx) emission mitigation - Islam, Aminul; Teo, Siow Hwa; Ng, Chi Huey; Taufiq-Yap, Yun Hin; Choong, Shean Yaw Thomas; Awual, Md. Rabiul (Elsevier, 2022)
Great interest has been directed toward developing catalytic desulfurization and denitrification to remove toxic or environmentally harmful gases before atmospheric emission. The burning of fossil fuels produces sulfur dioxide (SO2) and nitrogen oxides (NOX). The most cost-effective technologies for reducing SOx and NOx emissions are imperative to mitigate greenhouse gas emissions produced by burning fossil fuels. A huge number of the research paper was published on greenhouse gas mitigation technology over the past two decades, which demonstrates both its importance and its rapid advancement. The various interested research communities would benefit greatly from a review covering key features of new and advanced SOx/NOx mitigation techniques. Thus, the leading SOx and NOx mitigation technologies available for emission and cleaning control of coal-fired power plant flue gases using novel materials have been reviewed in this study. Various physical and chemical properties in the solid catalytic desulfurization and denitrification process, specifically the structure and active functional groups as well as the stability of the catalyst were highlighted. Research directions for overcoming the challenges involved in SOx and NOx mitigation using solid catalysts/sorbents interface adsorption were suggested. Then the results are clear and compelling with reducing SOx and NOx emissions to mitigate greenhouse gas emissions which will contribute to the practical value of scientific knowledge.